The effect of increasing jump steps on stance leg joint kinetics in bounding - Kariyama, Y.; Hobara, H.; Zushi, K. (International Journal of Sports Medicine, 2018)
Jump distance per step in bounding exercises from the standing position increases with increasing number of steps. We examined the hypothesis that the joint kinetic variables of the stance leg would also increase accordingly. Eleven male athletes (sprinters and jumpers) performed bounding exercise, starting from the double-leg standing posture, and covered the longest distance possible by performing a series of seven forward alternating single-leg jumps. Kinematic and kinetic data were calculated using the data by a motion capture system and force platforms. Hip extension joint work were decreased at third step (1st: 1.07±0.22, 3rd: 0.45±0.15, 5th: 0.47±0.14?J•kg-1; partial ?2: 0.86), and hip abduction joint power were increased (1st: 7.53±3.29, 3rd: 13.50±4.44, 5th: 21.37±9.93?W•kg-1; partial ?2: 0.58); the knee extension joint power were increased until the third step (1st: 14.43±4.94, 3rd: 17.13±3.59, 5th: 14.28±2.86?W•kg-1; partial ?2: 0.29), and ankle plantar flexion joint power increased (1st: 34.14±5.33, 3rd: 37.46±4.45, 5th: 40.11±5.66?W•kg-1; partial ?2: 0.53). These results contrast with our hypothesis, and indicate that increasing the jump distance during bounding exercises is not necessarily accompanied by increases in joint kinetics of stance leg. Moreover, changes in joint kinetics vary at different joints and anatomical axes.